Peningkatan Hasil Belajar Akidah Akhlak Materi Aliran dan Tokoh Ilmu Kalam melalui Metode Snowball Throwing di Madrasah Aliyah Salafiyah Kota Cirebon - Istijabah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
This study aims to improve the learning outcomes of Akidah Akhlak through the Snowball Throwing Method. The subject of the study was a grade XI IPA 1 MA Salafiyah Cirebon student in the 2017/2018 school year. This study uses the Class Action method through two cycles. Data is collected through tests, observations, and documentation. The results showed that from the pre-cycle process, cycle I, and cycle II experienced a significant increase. Pre-cycle and cycle I results were at 45.7% percentage, increasing to 97.1% in cycle II. While the average grade value has an average score of 72.4 on pre-cycle, 74.9 on cycle I, and 90.7 on cycle II. Snowball throwing method can improve students' learning outcomes in MA Salafiyah Cirebon.